MLPA Application in Clinical Diagnosis of DMD/BMD in Shanghai. Issue 5 (17th August 2014) - Ji, Xing; Zhang, Jingmin; Xu, Yan; Long, Fei; Sun, Wei; Liu, Xiaoqin; Chen, Yingwei; Jiang, Wenting
<x xml:space="preserve">Abstract</x> Background Duchenne and Becker muscular dystrophy (DMD/BMD) are X‐linked recessive disorders caused by mutation in dystrophin gene. We reported 3‐year clinic experience from a single hospital in Shanghai using multiplex ligation dependent probe amplification (MLPA) assay to detect DMD mutations. Methods Four hundred and fifty‐one males and 184 females, who were clinically diagnosed as DMD/BMD patients or carriers at our hospital's outpatient clinic, were collected and performed with MLPA to detect DMD gene mutations. Results Seventeen novel mutation points not reported in the Leiden Muscular Dystrophy pages were identified in this study. We found that the most frequent deletion spots ranged from exon45 to exon52, and exon2, exon19 were the two most frequently detected duplication spots. Conclusion The results of our study confirmed MLPA as an efficient clinical method for detecting DMD gene mutations in DMD/BMD patients. Single exon mutation detected by MLPA should be verified by other methods, and we should emphasize that only precise clinical molecular diagnosis can lead to the feasibility of prenatal diagnosis.